Development and Psychometric Assessment of the Consumer Socio-Cultural Premises Scale in Mexico - Francisco Leonardo Soler-Anguiano; Rolando Díaz-Loving; Alejandra del Carmen Domínguez-Espinosa (Psychology in Russia: State of Art)
Background. Investigating the complexities of consumer behaviour requires an understanding of the sociocultural contexts that shape individual preferences and purchasing patterns. Factors such as family dynamics, community norms, and cultural values emphasise the importance of exploring the influence of sociocultural premises. These forces are continuously negotiated within the evolving trends of the global consumer culture. As a result, it is essential to recognise that each group has unique values and needs that must be acknowledged. Objective. This study aims to explore, develop, and assess psychometric properties and evidence of a measure assessing consumer sociocultural premises from an ethnopsychology approach, to identify distinctive elements shaping purchasing patterns based on social norms. Design. A mixed-methods research design was employed to gather qualitative and quantitative data for a comprehensive analysis. First, sociocultural norms were extracted through focus group discussions. Building upon these identified premises, the subsequent study developed a scale wherein scale items were created, and their psychometric properties were evaluated through exploratory and confirmatory factor analyses. Results. The first study identified sociocultural premises related to family, gender roles, self-sacrifice, product, and hedonism that shape consumer behaviour. In the second study, these elements were incorporated into the initial set of scale items, which were then refined through expert review, pilot testing, and statistical analyses. Results revealed a seven-factor structure reflecting the key socio-cultural premises identified in the focus groups. The scale demonstrated strong internal consistency and adequate psychometric properties evidence. Conclusion. The findings of this study underscore the significance of sociocultural factors in shaping individual purchasing behaviour, emphasising the need for a measurement tool that captures culturally specific purchasing beliefs and universal factors. This research contributes to the existing body of knowledge on social dynamics and consumer behaviour, providing valuable insights for future studies and practical applications in the field.